Sthenelais boa ... - Barnich, Ruth; Haaren, Ton Van (Zenodo, 2021)
Sthenelais boa (Johnston, 1833) (emended) Figs 3–4, 5A–D Sigalion boa Johnston, 1833: 322, fig. 42. Sigalion Idunae Rathke, 1843: 150–155, pl. 9 figs 1–8 (fide Malmgren 1866). Sthenelais ctenolepis Claparède, 1868: 398, pl. 4 fig. 1a–k, pl. 6 fig. 2 (see Barnich & Fiege 2003). Sthenelais fuliginosa Claparède, 1868: 404, pl. 4 fig. 2a–h (see Barnich & Fiege 2003). Sthenelais minor Pruvot & Racovitza, 1895: 465, pl. 20 figs 111–121. Syn. nov. ? Sigalion Estellae Guérin-Méneville, 1843: 2, pl. 1 fig. 1 (see Fauvel 1923; however, description insufficient). ? Sthenelais Audouinii Quatrefages, 1866: 275 (see Fauvel 1923; indeterminable according to Chambers & Muir 1997, description by Quatrefages referring to Leanira or Sthenelais ). ? Sthenelais Edwardsii Quatrefages, 1866: 273 (see Fauvel 1923; however, description insufficient). ? Sthenelais Leidyi Quatrefages, 1866: 278 (see Pettibone 1963; however, status questionable, see remark below). Sthenelais boa – McIntosh 1900: 408, pl. 26 figs 7–8, ... : Published as part of Barnich, Ruth & Haaren, Ton Van, 2021, Revision of Sthenelais Kinberg, 1856, Fimbriosthenelais Pettibone, 1971 and Eusthenelais McIntosh, 1876 (Polychaeta, Sigalionidae) in the Northeast Atlantic, pp. 138-171 in European Journal of Taxonomy 740 on pages 149-154, DOI: 10.5852/ejt.2021.740.1287, http://zenodo.org/record/4649646 ...